2008
DOI: 10.1089/end.2007.0268
|View full text |Cite
|
Sign up to set email alerts
|

What Radiation Exposure Can a Patient Expect During a Single Stone Episode?

Abstract: In this study the median radiation dose per stone episode was calculated at 5.3 mSv, with higher doses in those with renal stones and those who required CT scans and other interventions. Monitoring and reduction of radiation exposure is advised for all patients presenting with urolithiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 12 publications
1
16
0
3
Order By: Relevance
“…Up to 50% of stone formers will suffer a recurrence within 10 years 2 and may undergo many CT. 65,66 Katz et al 66 reported on the use of CT stone protocols for 4,562 patients during a 6-year period. They found that a single stone protocol CT imparted an effective dose between 6.5 and 8.5 mSv, with 4% of patients obtaining 3 or more CT examinations with a cumulative radiation dose between 10.5 and 153.7 mSv.…”
Section: Resultsmentioning
confidence: 99%
“…Up to 50% of stone formers will suffer a recurrence within 10 years 2 and may undergo many CT. 65,66 Katz et al 66 reported on the use of CT stone protocols for 4,562 patients during a 6-year period. They found that a single stone protocol CT imparted an effective dose between 6.5 and 8.5 mSv, with 4% of patients obtaining 3 or more CT examinations with a cumulative radiation dose between 10.5 and 153.7 mSv.…”
Section: Resultsmentioning
confidence: 99%
“…Ayrıca böbrek yerleşimli taşlarda ultrasonografik (US) odaklama da; azımsanmayacak oranlarda başarıyla kullanılmaktadır (7,21). SWL tedavisi sırasında alınan iyonize radyasyon dozu böbrek başına ortalama 6.8mSv olarak hesaplanmıştır (30). Taşı olan çocuklarda tanıda ve takiplerde kullanılacak görüntüleme yöntemlerinin seçimi de önem arz etmektedir.…”
Section: çOcuklukunclassified
“…NKBT tanının açık olmadığı veya tedavi planlamasında anatomik detay gerekliliğinde yaptırılmalıdır; çünkü maruz kalınan radyasyon dozu single detector NKBT'de 6.5 mSv, multidetector NKBT'de 8.6 mSv ve düşük doz NKBT'de 1.5 mSv olarak hesaplanmıştır. İşte bu nedenle çocuklarda NKBT gerektiğinde ALARA (as low as reasonably achievable) prensibine göre mutlaka düşük doz protokol tercih edilmelidir (30). Yukarıda basedilen tüm bu nedenlerle SWL'nin, erişkinlerde uygulanması 1984 yılın-da U.S. Food and Drug Administration (FDA) tarafından onaylanmasına rağmen, çocuklarda uygulanmasına dair halen bu kurumun onayı bulunmamaktadır.…”
Section: çOcuklukunclassified
“…John et al [42] evaluated radiation exposure for patients being evaluated and treated during a single complete stone episode from the time of diagnosis to stone-free status. In this retrospective cohort study, KUB and IVU were performed initially, and CT was used in select cases or if there was a contrast allergy.…”
Section: Radiation Exposure In the Evaluation Of Stone Diseasementioning
confidence: 99%